2018
DOI: 10.1002/prep.201800150
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Plate Fracture from Detonation Wave Interaction

Abstract: The interaction of detonation waves was widely used in warhead design due to its ability to generate local high‐pressure regions. In this paper, the detonation interaction was investigated by experiments and finite element (FE) models. Experiments were conducted first to capture the fundamental dynamic fracture and fragmentation patterns and they served as a basis of validation for both the FE and analytical models. According to fracture surface, shear fracture is prior mechanism for steel‐plate fragmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…The equations are widely used for metallic materials as numerous efforts have been exerted to determine these parameters. The material properties and parameters used for aluminum and steel [23] are summarized in Table 5. Figure 6b, a hemispherical shock wave is formed when the projectile impacts liquid hydrazine, which is consistent with Figure 6a.…”
Section: Appl Sci 2019 9 X For Peer Review 10 Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…The equations are widely used for metallic materials as numerous efforts have been exerted to determine these parameters. The material properties and parameters used for aluminum and steel [23] are summarized in Table 5. Figure 6b, a hemispherical shock wave is formed when the projectile impacts liquid hydrazine, which is consistent with Figure 6a.…”
Section: Appl Sci 2019 9 X For Peer Review 10 Of 16mentioning
confidence: 99%
“…The equations are widely used for metallic materials as numerous efforts have been exerted to determine these parameters. The material properties and parameters used for aluminum and steel [23] are summarized in Table 5. Figure 6a presents the shock wave pressure and duration in liquid hydrazine calculated by Zeus, and Figure 6b shows the pressure nephogram of the shock wave obtained by ANSYS/LS-DYNA software at 0.10 μs, 0.25 μs, 0.32 μs, 0.50 μs, 0.70 μs, and 0.88 μs s. t = 0 indicates the moment when the projectile contacts with liquid hydrazine, and t = 0.88 μs indicates the moment when the projectile completely enters liquid hydrazine.…”
Section: Appl Sci 2019 9 X For Peer Review 10 Of 16mentioning
confidence: 99%
“…These equations are widely used for metallic materials because numerous efforts have been exerted to determine the parameters. The material properties and parameters used for aluminum [14] and steel [19] are summarized in Table 2. The air was modeled using the constitutive equation of MAT_NULL and the state equation of EOS_LINEAR_POLYNOMIAL [14].…”
Section: Validation Of Simulation Modelmentioning
confidence: 99%
“…Figure19. Attenuation curves of the translation velocity when the debris impacted the satellite tank with angular velocities of wy = 1 rad/μs, wy = 2 rad/μs, wy = 3 rad/μs, wy = 4 rad/μs, and wy = 5 rad/μs.…”
mentioning
confidence: 99%
“…Liu et al [26] analyzed the collision process of detonation waves in a double-layer-shaped charge, and a mathematical model for the propagation and interaction of detonation waves was established. Li et al [25] examined the effects of pressure and the region of the Mach wave zone on the annular multi-point initiation. They concluded that the range of Mach reflection decreased and the pressure of the Mach wave increased as the initiation diameter increased.…”
Section: Introductionmentioning
confidence: 99%